2015
DOI: 10.1016/j.tibs.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Changed in translation: mRNA recoding by −1 programmed ribosomal frameshifting

Abstract: Programmed S1 ribosomal frameshifting (S1PRF) is an mRNA recoding event commonly utilized by viruses and bacteria to increase the information content of their genomes. Recent results have implicated S1PRF in quality control of mRNA and DNA stability in eukaryotes. Biophysical experiments demonstrated that the ribosome changes the reading frame while attempting to move over a slippery sequence of the mRNA -when a roadblock formed by a folded downstream segment in the mRNA stalls the ribosome in a metastable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
124
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 84 publications
1
124
0
Order By: Relevance
“…Many clinically relevant antibiotics target the ribosome, and induce errors in all stages of the decoding process. Furthermore, while programmed ribosomal frameshift (PRF) is exploited by some viruses (and their host cells) to control the amount of their structural and enzymatic proteins available for viral particle assembly (Brierley, 1995; Caliskan et al, 2015; Dinman, 1995; Dunkle and Dunham, 2015), slippage of ribosomes in either direction (5’ (−1) or 3’ (+1)) will produce a truncated protein, or lead to mRNA degradation via nonsense-mediated decay (Belew and Dinman, 2015). …”
Section: (Introduction)mentioning
confidence: 99%
“…Many clinically relevant antibiotics target the ribosome, and induce errors in all stages of the decoding process. Furthermore, while programmed ribosomal frameshift (PRF) is exploited by some viruses (and their host cells) to control the amount of their structural and enzymatic proteins available for viral particle assembly (Brierley, 1995; Caliskan et al, 2015; Dinman, 1995; Dunkle and Dunham, 2015), slippage of ribosomes in either direction (5’ (−1) or 3’ (+1)) will produce a truncated protein, or lead to mRNA degradation via nonsense-mediated decay (Belew and Dinman, 2015). …”
Section: (Introduction)mentioning
confidence: 99%
“…SD motifs have well-characterized roles in frameshifting in bacteria: in the dnaX gene, an internal SD motif contributes to −1 frameshifting at a slippery sequence followed by an mRNA hairpin (Larsen et al, 1994). In vitro studies on this system have shown that the downstream hairpin blocks translocation (Caliskan et al, 2014; Chen et al, 2014), resulting in a kinetic pause; this in turn allows different codons and reading frames to be sampled on the slippery sequence (Caliskan et al, 2015; Yan et al, 2015). In the metastable state where the ribosome slips on the message, the SD motif stabilizes the interaction with the mRNA in a new position.…”
Section: Discussionmentioning
confidence: 99%
“…Translational readthrough of stop codons, a measure of translation fidelity, is increased in triad deletion mutants 21 . The ability of ribosomes to shift translational reading frame, particularly −1 frameshifting, is a capacity used to produce alternative proteins from the same mRNA transcript or to regulate premature termination 22 . −1 frameshifting is decreased in triad deletion mutants 23 .…”
Section: Introductionmentioning
confidence: 99%